HUBUNGAN POSTUR KERJA DAN FREKUENSI MENGAYUN DENGAN KELUHAN ANGGOTA TUBUH BAGIAN ATAS PADA PENAMBANG PASIR TRADISIONAL DI KECAMATAN SRUMBUNG KABUPATEN MAGELANG. - Padang Purwosusilo; Ida Wahyuni; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Musculosceletal disorders (MSDS) is a symptom associated with muscles, tendons, ligaments, cartilage, nervous system, bones and blood vessels. Factors cause of MSDS is wrong work postures, repetitive movements that are too frequent and longer working lives that will cause complaints in skeletal muscle that will have an impact on the decline in labor productivity. The purpose of this study was to determine the relationship work posture and swing frequency with complaints rappid upper limb in traditional sand miners in the district Srumbung Magelang regency. Complaints musculosceletal disorders in this study was measured by using a mapping nordic body map. This study is a quantitative study with cross sectional approach. The samples used on this research is total sampling of the entire population of workers in traditional sand mining the number of workers of 38 workers. Analysis of data using univariate and bivariate analysis with Chi-square test. Bivariate analysis showed that there is a correlation between work posture with complaints musculosceletal disorders (p-value 0.04) and there was no correlation between the frequency swing with complaints musculosceletal disorders (p-value 0.1). the conclusion of this study is the relationship among the variables that work with complaints musculosceletal posture disorders. Researchers also suggest the traditional sand miners to stretch before and interrupted during their work in order to increase the rate of muscle flexibility, thereby reducing the potential for lower back pain or musculosceletal disorders.